2012
DOI: 10.1061/(asce)ei.1943-5541.0000075
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Benchmark Indicator for Managerial Competences in Construction at the Graduate Level

Abstract: Alta gerencia con amplia experiencia en psicología organizacional liderando procesos de reclutamiento, selección, contratación, desarrollo y temas relacionados a la administración de personal, manejo de clientes internos y externos de la compañía. Contacto:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
1
30
0
7
Order By: Relevance
“…In the field of construction management, the authors previously proposed and developed a theoretical model (Pellicer et al 2009, Yepes et al 2012, which is briefly explained in the next section and will be applied later in the study.…”
Section: Figure 1: Proposed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the field of construction management, the authors previously proposed and developed a theoretical model (Pellicer et al 2009, Yepes et al 2012, which is briefly explained in the next section and will be applied later in the study.…”
Section: Figure 1: Proposed Methodsmentioning
confidence: 99%
“…First, each academic program must facilitate not only online access to its curriculum, but the information must also be understandable and include a detailed inventory of the courses, their credits (or relative weights), and their descriptors. An in-depth explanation of this exploratory study can be found in Yepes et al (2012). It is important to note that the selected set of programs does not affect the method; it would not change with another set of programs using other selection criteria.…”
Section: Sample Of University Programsmentioning
confidence: 99%
See 3 more Smart Citations